KONSENTRASI KEPEMILIKAN, STRUKTUR DEWAN KOMISARIS DAN RISIKO KREDIT BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Atika, Rulia; Husaini, Husaini; Ilyas, Fitrawati (JURNAL FAIRNESS, 2020)
This study aims to find empirical evidence regarding the influence of ownership concetration and board structure on credit risk. The sample of this study is the banks listed on the Indonesia Stock Exchange. Board structure proxied by the board size, proportion of independent commissioners, the presence of foreign commissioners, audit committee and risk management committee. The hypothesis was tested using multiple linear regression. This study found that ownership concentration 25%, ownership concentration 50% and audit committee have a positive effect on credit risk, Proportion of independent commissioners and risk managment committee have negatively affect on credit risk. While the. ownership concentration 10%, board size and the presence of foreign commissioners have no affect on credit risk.